Anti-Herpetic and Anti-Dengue Activity of Abietane Ferruginol Analogues Synthesized from (+)-Dehydroabietylamine (2009)
ABSTRACT: The abietane-type diterpenoid (þ)-ferruginol (1), a bioactive compound isolated from several plants, has attracted much attention as consequence of its pharmacological properties, which includes antibacterial, antifungal, antimicrobial, cardioprotective, anti-oxidative, anti-plasmodial, leishmanicidal, anti ulcerogenic, anti-inflammatory and antitumor actions. In this study, we report on the antiviral evalua tion of ferruginol (1) and several analogues synthesized from commercial (þ)-dehydroabietylamine. Thus, the activity against Human Herpesvirus type 1, Human Herpesvirus type 2 and Dengue Virus type 2, was studied. Two ferruginol analogues showed high antiviral selectivity index and reduced viral plaque-size in post-infection stages against both Herpes and Dengue viruses. A promising lead, com pound 8, was ten-fold more potent (EC50 ¼ 1.4 mM) than the control ribavirin against Dengue Virus type 2. Our findings suggest that the 12-hydroxyabieta-8,11,13-triene skeleton, which is characteristic of the diterpenoid ferruginol (1), is an interesting molecular scaffold for development of novel antivirals. In addition, the cytotoxic and antifungal activities of the synthesized ferruginol analogues have also been investigated. ©20155 Elsevier Science. All rights reserved.